Methodological to IFPRI database for GHG emissions from agriculture by country, commodity, and source, 2016 - Laborde Debucquet, David; Mamun, Abdullah; Martin, Will; Piñeiro, Valeria; Vos, Rob (International Food Policy Research Institute, 2021)
For this study, we created a new database of emissions in agricultural production. FAOSTAT presents vectors of data on emissions by type and by commodity for each country, but we need the full matrix of emissions by type, commodity, and source to allow us to consider changes in emissions by type in production of each commodity, such as reductions in emissions from enteric fermentation in beef production. Wherever possible, we derived this full matrix by reverse engineering the FAO emission data to ensure that the total matched the FAOSTAT estimates. Where this was not possible, as in the case of emissions from pesticides, we used a similar IPCC Tier 1 methodology to generate comparable estimates.